PENGARUH FAKTOR-FAKTOR REFORMASI PERPAJAKAN, SISTEM PENGENDALIAN INTERN, DAN PROFESIONALISME PEGAWAI TERHADAP PENINGKATAN PENERIMAAN PAJAK (Studi pada Kantor Wilayah Direktorat Jenderal Pajak Jawa Barat I) - Nur Hidayat (Indonesian Journal of Economics and Business, 2011)
The main subject of this research is a decrease of tax revenue in Directorate General of Taxes (DJP), suspected under the influence of employee professionalism. DJP needs reform of, legislation, organization and  administration structure, database and information technology systems, and quality, competence and integrity of the employee, and implementation of effective internal control system. According to the statement before, the researcher was interested in conducting a research entitled "The Influence of Tax Reform Factors, Internal Control Systems, and Employee Professionalism on Increasing Tax Revenue".            The research was aimed at testing: (1) the influence level of tax reform factors and internal control systems on employee professionalism either partialy and simultaneously, and (2) the  influence of tax reform factors, internal control system, and employee professionalism on an increase of tax revenue partialy and simultaneously.            The research used a survey method, conducted in Tax Payers District Tax Office (KPP) Directorate General of Taxes West Java I by taking the population of this research entirely (census). Primary data was collected through the questionnaire, completed by employees of KPP. 236 questionnaires have been sent to the population however, only 212 questionnaires could be presented. First of all before using data, the validity and reliability test were conducted to test the hypothesis. Secondary data was also used, it was directly taken from the KPPs which are the target and realisation of tax revenue in 2007, 2008, and 2009. The data analysis of the hypothesis testing used description and path analysis using Lisrel 8.70 software.            As conclusion the research indicates: (1) the tax reform factors and internal control system have a positive and significant influence on employee professionalism  partialy and simultaneously, and (2) the tax reform factors, internal control system, and employee professionalism  have a positive and significant influence on an increasing tax revenue partialy and simultaneously.